Resting respiratory lung volumes are "healthier" than exercise respiratory volumes in different types of palliated or corrected congenital heart disease. Issue 3 (17th January 2020) - Fabi, Marianna; Balducci, Anna; Cazzato, Salvatore; Aceti, Arianna; Gallucci, Marcella; Di Palmo, Emanuela; Gargiulo, Gaetano; Donti, Andrea; Lanari, Marcello
Abstract: Aims: Cardiac surgery has improved life expectancy of patients with congenital heart diseases (CHDs). Exercise capacity is an important determinant of survival in patients with CHDs. There is a lack of studies focusing on the role of resting respiratory performance in reducing exercise tolerance in these patients. Objectives: To determine the prevalence and severity of respiratory functional impairment in different types of corrected/palliated CHDs, and its impact on an exercise test. Materials and Methods: Retrospective single‐center study involving 168 corrected/palliated patients with CHD and 52 controls. Patients CHD were divided into subgroups according to the presence of native pulmonary blood flow or total cavopulmonary connection (TCPC). All subjects performed complete pulmonary function tests and gas diffusion; patients with CHD also performed cardiopulmonary exercise test (CPX). Results: Mean values of lung volumes were within the normal range in all CHD groups. Comparing to controls, patients with the reduced pulmonary flow and with TCPC had the highest reduction in lung volumes. CPX was reduced in all groups, most severely in TCPC, and it was correlated to decreased dynamic volumes in all CHD groups except in TCPC. Younger age at intervention and number of surgical operations negatively affected lung volumes. Conclusions: Respiratory function is within the normal range in our patients with different CHDs at rest but altered in all CHDs during exercise when cardiorespiratory balance is likely to be inadequate. Comparing the different groups, patients with reduced pulmonary flow and TCPC are the most impaired.